2020
DOI: 10.33393/jcb.2020.2121
|View full text |Cite
|
Sign up to set email alerts
|

Exploring adipogenic and myogenic circulatory biomarkers of recurrent pressure injury risk for persons with spinal cord injury

Abstract: Purpose: To investigate linkages between circulatory adipogenic and myogenic biomarkers, gluteal intramuscular adipose tissue (IMAT), and pressure injury (PrI) history following spinal cord injury (SCI). Methods: This is an observational repeated-measures study of 30 individuals with SCI. Whole blood was collected regularly over 2-3 years. Circulatory adipogenic and myogenic gene expression was determined. IMAT was defined as above/below 15% (IMATd) or percentage (IMAT%). PrI history was defined as recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…However, there was no relationship between fat infiltration and BMI. This is consistent with Bogie et al (2020) . Time since injury is a much stronger predictor of IMAT, suggesting that the process occurs at some point after injury, likely as a result of disuse and atrophy, in response to myogenic and adipogenic markers identified in ( Bogie et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, there was no relationship between fat infiltration and BMI. This is consistent with Bogie et al (2020) . Time since injury is a much stronger predictor of IMAT, suggesting that the process occurs at some point after injury, likely as a result of disuse and atrophy, in response to myogenic and adipogenic markers identified in ( Bogie et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with Bogie et al (2020) . Time since injury is a much stronger predictor of IMAT, suggesting that the process occurs at some point after injury, likely as a result of disuse and atrophy, in response to myogenic and adipogenic markers identified in ( Bogie et al, 2020 ). BMI (i.e., body weight and height) was self-reported in this study, so the accuracy of BMI values is unknown.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This preliminary work has shown the effect of candidate single-nucleotide variants on IMAT accumulation and recurrent PI risk. The authors have previously shown that varying levels of circulatory biomarkers, including FABP4 and FABP3 , may be indicative of recurrent PI risk 24,29–31 . Further, genetic biomarkers, specifically those related to fatty metabolism, may indicate which persons with SCI are at highest risk of recurrent PIs 32 …”
Section: Discussionmentioning
confidence: 99%